Integration of Information, Communication and Automation technologies in Housing Rehabilitation - Eloy, S. (2010)
This paper addresses the integration of Information, Communication and Automation Technologies (ICAT) in the dwelling space so as to meet the needs of users. ICAT systems can have a very important role in contemporary dwellings because of the benefits they bring to residents both from the ecological and social perspectives. The paper describes an ongoing PhD research that is concerned with the rehabilitation of the existing housing stock to fulfill the new needs of dwellers in the current Information Society and with the consequences of the integration of ICAT in dwellings. The research aims at the development of a rehabilitation methodology devised to enable architects to take user needs and requirements in home automation matters into account from the beginning of the architectural design process. Ultimately, the proposed methodology will enable a compatible and properly integration of ICAT in architectural spaces and in their built envelope. The incorporation of new housing functions calls for a new approach to the design of domestic space, in which the diversity of conventional spaces must interact with the inclusion of new multifunctional areas that accommodate activities such as telework and telehealth in order to respond to the growing demand of information access and of comfort at home. After a brief description of the general methodology, this paper focuses on the ecological and social benefits that ICAT brings to the environment, the construction industry, and the dwellers. Then it describes the impact of ICAT integration on the functional organization of the dwelling and on construction elements and it lays down the strategies for an adequate integration from these two viewpoints.